Genetic dissection of the Drosophila BLOC-1 complex reveals distinctions in synaptic localization and homeostatic plasticity. - Stark, R.; Dehn, C.; Abadi, N.; Xiong, Y.; Porter, L.; Chen, X.; Dickman, D. (Molecular Biology of the Cell, 2025)
Neuronal trafficking pathways must operate with high fidelity and speed, adapting to the dynamic demands of synaptic activity to maintain stable functionality. The biogenesis of lysosome-related organelles complex 1 (BLOC-1) is an attractive candidate to stabilize synaptic function during such challenges. BLOC-1 is an evolutionarily conserved protein complex composed of eight subunits involved in vesicle trafficking. In the nervous system, the BLOC-1 is associated with neurodevelopmental diseases and synaptic plasticity. However, the functions of each BLOC-1 component remain enigmatic. Here, we use CRISPR to mutate each Drosophila BLOC-1 gene to investigate roles in synaptic growth, function, and homeostatic plasticity. First, we show that BLOC-1 mutations are viable, with no defects in synaptic growth, morphology, or baseline function. We then demonstrate distinct synaptic localization patterns of BLOC-1 components. Finally, we show that only two of the eight BLOC-1 components, dysbindin and snapin, are necessary for presynaptic homeostatic potentiation. These results indicate separable functions and distinct synaptic localization patterns of BLOC-1 subunits, and a need to reconsider predictions made from biochemical models of BLOC-1.